Critical insights on fungal contamination in schools: a comprehensive review of assessment methods - Renata Cervantes; Renata Cervantes; Pedro Pena; Pedro Pena; Bruna Riesenberger; Margarida Rodriguez; Drew Henderson; Sara Gonçalves; Enas Newire; Enas Newire; Clara Pogner; Heidi Salonen; et al. (Frontiers in Public Health)
This review addresses the increasing problem of fungal contamination in schools, which has a profound impact on indoor air quality and student health. Fungal contamination creates health problems such as respiratory problems, allergies, which can be particularly harmful in schools (e.g., Aspergillus fumigatus and Fusarium sp. are especially important as they are a well-known indoor allergens and can induce serious respiratory diseases). The aim of this study is to determine the effect of geographic location as well as season of filamentous fungi in school context. Through a comprehensive screening of 6,659 articles, 47 studies were selected for data extraction, detailing sampling techniques, analysis methods, climatic conditions, and relevant fungal species. The study highlights the importance of regularly measuring IAQ and utilizing both active and passive sampling methodologies in addition to molecular genetic analysis to complement identification and improve comparability across studies. A targeted monitoring is also proposed for species such as Aspergillus fumigatus (Aspergillus section Fumigati), Fusarium sp., and Mucorales order, which are therapeutically relevant, as well as Stachybotrys atra and Aspergillus section Flavi, in terms of their toxicological potential. Additionally, the article discusses the importance of consistent data formatting for effective meta-analysis and the need for further research to inform regulatory frameworks protecting student health. Recommendations for minimizing fungal threats include evaluating building structure, ventilation, cleaning practices, and gathering information from parents about school activities. Overall, the study underscores the global health risks posed by fungi in schools and calls for extensive investigations combining various sampling and analytical techniques. Additionally, the article discusses the importance of consistent data formatting for effective meta-analysis and the need for further research to inform regulatory frameworks protecting student health. Recommendations for minimizing fungal threats include evaluating building structure, ventilation, cleaning practices, and gathering information from parents about school activities. Overall, the study underscores the global health risks posed by fungi in schools and calls for extensive investigations combining various sampling and analytical techniques.